Towards conflicting chronologies: a topographic insight following Reinhart Koselleck’s work - Svampa, Lucila (História da Historiografia: International Journal of Theory and History of Historiography, 2022)
This article considers the role that spatiality played in Koselleck’s work. With that aim, we will examine how the writer dealt with the relationship between historicity and spatiality. His few theorizations regarding this topic will be taken into account, as well as different concepts relevant to his work that evoke this partnership. Through an analysis of five terms, Zeitschichten, Erfahrungsraum, Erwartungshorizont, Standortbindung, and Utopie, we will show how spatiality holds a secondary position in relation to history and how they affect Koselleck’s theory of historical times.